TRANSFORMATION OF MSMES THROUGH PRODUCT INNOVATION; ANALYSIS OF LOCAL ECONOMIC EMPOWERMENT - Moh. Rosi; Riza Wahyu Utami; Neviyani Neviyani (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE - This research aims to explore and elaborate on business development strategies, including product innovation, financial management, and marketing strategies, as well as the socio-economic impact of the MSME "Kripik Rido Susi" in Silo Village, Jember.METHODOLOGY - This research is a qualitative descriptive study with a case study type. The data in this research were collected through observation, interviews, and documentation methods. The validity of the data was tested using method, source, and time triangulation.FINDING - The research results show that the product innovation strategy is carried out through the development of taste, packaging, and size, based on simple market research. Financial management is handled manually but consistently, with daily record-keeping and capital support from personal funds as well as village assistance. The marketing strategy combines conventional approaches (consignment sales at small shops and cooperatives) and digital methods (social media and marketplaces). The existence of these SMEs not only increases the household income of employees but also strengthens the social capital of the community through active participation and pride in local products. These findings affirm that MSMEs based on local potential can be an effective instrument in creating economic independence for rural communities. This research provides empirical contributions to the literature on local economic development and offers a model of empowerment practices that can be replicated in similar regions